Kinematics of a Hot Massive Accretion Disk Candidate - Beuther, H.; Walsh, Andrew (Institute of Physics Publishing, 2008)
Characterizing rotation, infall, and accretion disks around high-mass protostars is an important topic in massive star formation research. With the Australia Telescope Compact Array and the Very Large Array, we studied a massive disk candidate at high angular resolution in ammonia [NH3(4, 4) and (5, 5)] tracing the warm disk but not the envelope. The observations resolved at ~0.4" resolution (corresponding to ~1400 AU) a velocity gradient indicative of rotation perpendicular to the molecular outflow. Assuming a Keplerian accretion disk, the estimated protostar-disk mass would be high, similar to the protostellar mass. Furthermore, the position-velocity diagram exhibits additional deviation from a Keplerian rotation profile that may be caused by infalling gas and/or a self-gravitating disk. Moreover, a large fraction of the rotating gas is at temperatures >100 K, markedly different from typical low-mass accretion disks. In addition, we resolve a central double-lobe centimeter continuum structure perpendicular to the rotation. We identify this with an ionized, optically thick jet. Resorting Query Results http://adsabs.harvard.edu/cgi-bin/nph-abs_connect 73